Thrombomodulin Modulates the Mitogenic Response to Thrombin of Human Umbilical Vein Endothelial Cells - Lafay, Monique; Laguna, Reyes; Le Bonniec, Bernard F.; Lasne, Dominique; Aiach, Martine; Rendu, Francine (Thrombosis and Haemostasis, 1998)
Thrombin interacts with its receptor and thrombomodulin on endothelial cells. We evaluated the respective roles of these two proteins on human umbilical vein endothelial cell (HUVEC) growth by comparing thrombin, S195A (a mutant thrombin in which the serine of the charge stabilizing system had been replaced by alanine), and the receptor activating peptide (TRAP). Thrombin and TRAP induced DNA synthesis (half maximal cell proliferation with 5 nM and 25 μM, respectively), whereas S195A thrombin was inactive, inferring that growth is mediated through the thrombin receptor. Surprisingly, cells stimulated by TRAP exhibited a maximal proliferation twice greater than that obtained with thrombin. Combination of thrombin and TRAP resulted in a mitogenic response higher than by thrombin alone, but lower than by TRAP alone. The role of thrombomodulin was evaluated by adding an anti-thrombomodulin antibody, which prevents formation of the thrombin-thrombomodulin complex. Antibody did not interfere with cell proliferation induced by TRAP, but enhanced that induced by thrombin. We conclude that formation of the thrombin-thrombomodulin complex restrains HUVEC proliferation mediated through the thrombin receptor.